2014
DOI: 10.1063/1.4876115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of La3+ substitution with Gd3+ on the resistive switching properties of La0.7Sr0.3MnO3 thin films

Abstract: This study demonstrated that the resistive switching voltage of perovskite manganite material could be controlled by A-site cation substitution in “A” MnO3 perovskite manganite structure. A partial substitution of La3+ in La0.7Sr0.3MnO3 with smaller cation Gd3+ induced A-site vacancy of the largest Sr2+ cation with surface segregation of SrOy due to ionic size mismatch, and the induced vacancies reduced migration energy barrier. The operating voltage decreased from 3.5 V to 2.5 V due to a favorable condition f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…For the Sr 3d 5/2 spectra, two peaks are observed at ca. 133.3 eV (Sr1) and 131.3 eV (Sr2), corresponding to those in SrO-like secondary phases [31] and perovskite lattice [32][33][34] respectively. Roughly, the Sr1/Sr2 ratio is decreasing from LSMO-0-LSMO-4, indicating more segregation of strontium at higher annealing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…For the Sr 3d 5/2 spectra, two peaks are observed at ca. 133.3 eV (Sr1) and 131.3 eV (Sr2), corresponding to those in SrO-like secondary phases [31] and perovskite lattice [32][33][34] respectively. Roughly, the Sr1/Sr2 ratio is decreasing from LSMO-0-LSMO-4, indicating more segregation of strontium at higher annealing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic nanoparticles (MNPs) display physical and chemical properties different those found in their corresponding bulk materials. These properties make them attractive in widespread applications such as energy, electronics, sensor designs of all kinds, catalysts, magnetic refrigeration, optics, and in various biomedical applications [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Valence band spectra for perovskite oxides doped with different A‐site ions radius are shown in Figure b. It is mainly associated with contributions from the bonding states of Mn 3d–O 2p, O 2p nonbonding states, Mn 3d t 2g states and Mn e g states at ≈6.0, ≈3.2, ≈1.8, and ≈0.5 eV, respectively . It can be found that the increase in BO hybridization will contribute to the shift of O 2p nonbonding states toward the Fermi Level.…”
Section: Resultsmentioning
confidence: 99%